Before the Cult of Equity: New Monthly Indices of the British Share Market, 1829-1929 - Gareth Campbell; Richard S. Grossman; John D. Turner (Queen's University Belfast, Queen's Management School, 2019)
This paper presents new monthly capital gains, dividend yield, and total return indices for common equities quoted on British stock exchanges from 1829 to 1929. As well as creating an all-share index, we create a blue-chip index of the 30 largest companies, which we splice to the Financial Times 30 index to create a near-two-century-long (1829-2018) monthly share index. We use the new indices to examine the timing of British business cycles and compare the returns on home and foreign UK investment. We also construct indices for 22 domestic sectors, and calculate CAPM betas for each sector
Keywords: G10; N13; N14; N23; N24; 330